2017
DOI: 10.1016/j.biomaterials.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

BDNF gene delivery mediated by neuron-targeted nanoparticles is neuroprotective in peripheral nerve injury

Abstract: Neuron-targeted gene delivery is a promising strategy to treat peripheral neuropathies. Here we propose the use of polymeric nanoparticles based on thiolated trimethyl chitosan (TMCSH) to mediate targeted gene delivery to peripheral neurons upon a peripheral and minimally invasive intramuscular administration. Nanoparticles were grafted with the non-toxic carboxylic fragment of the tetanus neurotoxin (HC) to allow neuron targeting and were explored to deliver a plasmid DNA encoding for the brain-derived neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 47 publications
(48 reference statements)
0
70
0
Order By: Relevance
“…TMC with an average number molecular weight (Mtrue¯normaln) of 43.3 kDa, a degree of acetylation of 15.7% and a quaternization degree of 30.1% was used . To attain nanoparticle neurotropism, our group has been exploring the tethering of a pegylated HC fragment at the NPs surface . Consequently, thiol groups were introduced into the TMC polymer backbone (TMC SH ) by a previously described method .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TMC with an average number molecular weight (Mtrue¯normaln) of 43.3 kDa, a degree of acetylation of 15.7% and a quaternization degree of 30.1% was used . To attain nanoparticle neurotropism, our group has been exploring the tethering of a pegylated HC fragment at the NPs surface . Consequently, thiol groups were introduced into the TMC polymer backbone (TMC SH ) by a previously described method .…”
Section: Resultsmentioning
confidence: 99%
“…To attain nanoparticle neurotropism, our group has been exploring the tethering of a pegylated HC fragment at the NPs surface . Consequently, thiol groups were introduced into the TMC polymer backbone (TMC SH ) by a previously described method . During TMC SH complexation with plasmid DNA, the presence of thiol pending groups further contributes to the crosslinking of the polycation, stabilizing the resulting complexes, and allows the subsequent functionalization of the NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain‐derived neurotrophic factor (BDNF) is a neurotrophic factor and exists widely in the central nervous system (CNS), such as the hippocampus and cortex . BDNF plays crucial roles in survival, development, differentiation, and proliferation of brain neurons and repairs of injured nerve cells, which is mediated by the high‐affinity tropomysin‐related kinase B (TrkB) receptor . It has been reported that serum BDNF level is significantly low in depressed and diabetic patients and negatively correlated with the risk of depression .…”
Section: Introductionmentioning
confidence: 99%
“…development, differentiation, and proliferation of brain neurons and repairs of injured nerve cells, 7,8 which is mediated by the high-affinity tropomysin-related kinase B (TrkB) receptor. 9 It has been reported that serum BDNF level is significantly low in depressed and diabetic patients and negatively correlated with the risk of depression.…”
mentioning
confidence: 99%